The Determinants of Recall Event Timing of Contaminated Frozen Poultry Products in Retail Outlets in North-Central Nigeria - Emeka Solomon Fidelis; Moradeyo Adebanjo Otitoju; Park Odojoma Idisi; Ugochukwu Emmanuel Anazo; David Ocholi Achemu (Turkish Journal of Agriculture: Food Science and Technology)
This study examined the determinants of the recall event timing of contaminated frozen poultry products in retail outlets in North-Central Nigeria. It specifically identified the potential sources of frozen poultry product hazards in retail outlets, assessed the effectiveness of existing management strategies employed by retailers in preventing frozen poultry product recall in the outlets, and examined the factors influencing the recall event timing of contaminated frozen poultry products in retail outlets in the study area. Multistage sampling was employed to sample 202 respondents, and the data collected using a well-structured questionnaire was analyzed using descriptive statistics and discrete-time survival analysis. The results showed that most of the frozen poultry product retailers in outlets in the study area were men within the age bracket of 21 and 40 years and had a monthly restocking frequency of approximately four times. The result revealed that power outage was the highest potential source of hazards associated with frozen poultry products in retail outlets in the study area. Packaging poultry products before freezing, product labelling, and fridge segmentation are effective management strategies. The result of the factors influencing the recall event timing of contaminated frozen poultry products in retail outlets showed that retailing experience (P<0.01) and cooperative membership (P>0.01) significantly influenced the recall event timing of contaminated frozen poultry products in the study area. The study recommends that the Government offer tax incentives to retailers investing in reliable backup power solutions and provide guidelines for effective communication during recall events.